WINTER ROOST CHARACTERISTICS OF THE RIO GRANDE TURKEY IN SOUTH TEXAS - Harry H. Haucke (Wildlife Society Bulletin)
Abstract Winter roosts of Rio Grande turkeys (Meleagris gallopavo intermedia) were relatively close to permanent water. Roosts included above average size trees, were within close proximity to brush thickets and clearings, and contained relatively large numbers of trees and surface areas. Artificial roosts included windmills, corrals, camp houses, transmission lines, man‐made roosts, and artillery observation towers. Turkeys selected natural over artificial roosts when both were relatively numerous and of the same approximate heights.